2012
DOI: 10.5194/angeo-30-1411-2012
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a tropopause fold by MARA VHF wind-profiler radar and ozonesonde at Wasa, Antarctica: comparison with ECMWF analysis and a WRF model simulation

Abstract: Abstract. Tropopause folds are one of the mechanisms of stratosphere-troposphere exchange, which can bring ozone rich stratospheric air to low altitudes in the extra-tropical regions. They have been widely studied at northern mid-or high latitudes, but so far almost no studies have been made at mid-or high southern latitudes. The Moveable Atmospheric Radar for Antarctica (MARA), a 54.5 MHz wind-profiler radar, has operated at the Swedish summer station Wasa, Antarctica (73 • S, 13.5 • W) during austral summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…As was shown by previous studies (in the Northern Hemisphere Rao and Kirkwood, 2005, and in the Southern Hemisphere Mihalikova et al, 2012), folds can be positively identified in radar data by static-stability features which agree closely with layers of enhanced ozone measured by colocated in situ measurements by ozonesonde. This makes radar observations a powerful source of information about the occurrence rates of tropopause folds in areas without the possibilities of targeted ozonesonde measurement campaigns.…”
Section: Methodology and Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…As was shown by previous studies (in the Northern Hemisphere Rao and Kirkwood, 2005, and in the Southern Hemisphere Mihalikova et al, 2012), folds can be positively identified in radar data by static-stability features which agree closely with layers of enhanced ozone measured by colocated in situ measurements by ozonesonde. This makes radar observations a powerful source of information about the occurrence rates of tropopause folds in areas without the possibilities of targeted ozonesonde measurement campaigns.…”
Section: Methodology and Resultssupporting
confidence: 86%
“…Folding-like events, when measured wind speeds over the observation site do not reach decided 30 m s −1 , can in reality be tropopause folding events, which bring ozone-rich air mass from the lower stratosphere or extratropical transition layer (see e.g. Gettelman et al, 2011) to significantly lower altitudes, as suggested by radar measurements, ozonesonde observation and high-resolution modelling for a summer-fold at Wasa, Antarctica (Mihalikova et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations